High Expression of FCRLB Predicts Poor Prognosis in Patients With Colorectal Cancer - Wang, Xiaopeng; Lin, Ruirong; Zeng, Yi; Wang, Yi; Wei, Shenghong; Lin, Zhitao; Chen, Shu; Ye, Zaisheng; Chen, Luchuan (Frontiers in Genetics, 2022)
Background: Mining the prognostic biomarkers of colorectal cancer (CRC) has important clinical and scientific significance. The role of Fc receptor-like B (FCRLB) in solid tumors has never been reported or studied to our knowledge, and the prognostic role of FCRLB in CRC still awaits characterization. Methods: The potential prognostic factor FCRLB was screened out through TCGA database analysis. Then, its expression and associations with clinicopathological variables were assessed in the TCGA CRC cohort. The prognostic value of FCRLB was examined with multiple methods, such as the Kaplan-Meier method, ROC curve, time-dependent ROC analysis, and prediction model nomograms. Then, functional enrichment and annotation among the high and low FCRLB groups were achieved utilizing GO and KEGG analyses and GSEA. Fresh CRC tissue samples obtained clinically were used for the preparation of the tissue microarray and for further validation. Results: FCRLB was highly expressed in CRC tissues compared to normal tissues. Moreover, over-expression of FCRLB correlated with higher CEA levels, advanced T stage, N stage, M stage, AJCC stage, lymphatic invasion, perineural invasion, and incomplete resection (R1 and R2 resection). In addition, high expression of FCRLB was closely correlated to less favorable OS, DSS, and PFI. The analysis of CRC tissue microarray further confirmed the conclusion drawn from the TCGA data analysis. Conclusion: FCRLB is notably up-regulated in CRC tissues and may serve as a potential biomarker of CRC.